Plants around us - Dixon, Malcolm; Smith, Karen, 1958- (Mankato, Minn. : Smart Apple Media, 1999)
Describes different kinds of plants, the function of their leaves and roots, and how they grow. Includes related activities.
Includes index.
3.3
3-6
Keywords: Plants -- Juvenile literature; Botany -- Juvenile literature; Growth (Plants) -- Juvenile literature; Plants -- Experiments -- Juvenile literature; Botany -- Experiments -- Juvenile literature; Plants; Botany; Plants -- Experiments; Botany -- Experiments; Plants; Botany; Plants -- Experiments; Botany -- Experiments; Plants; Botany; Growth (Plants); Plants -- Experiments; Botany -- Experiments